EFFECT OF HIGH RISK PREGNANCY AWARENESS OF MOTIVATION FOR PREGNANT WOMEN TAKING PRENATAL CARE IN THE VILLAGE KEMBANG RINGGIT DISTRICT PUNGGING MOJOKERTO - Saudah, Noer; Achwandi, Ach. (JURNAL KEPERAWATAN SEHAT, 2016)
Antenatal period a condition to be prepared physically and psychologically for the birth and parenthood. The problem is often in the know many mother pregnace who did not regularly perform antenatale care it is contrary to the governments program to reduce during morbidity pregnancy and maternity low-high coverage KI and K4 cause mortality babys mother is still relatively high research objectives Knowing Effect of counseling about pregnancy a high risk maternal motivation do antenatal care in Kembang Ringgit Pungging District of Mojokerto. Pre-experimental research one group pretest-posttest design. Population more pregnant women in Kembang Ringgit Pungging District of Mojokerto number 40 sampling technique used purposive sampling with total sample of 36 respondents. measuring devices using the questionnaire pre test and post test. Variables consist of independent research is the influence of education on high risk pregnancy and pregnant women dependent motivation in doing antenatal care. Processing and Analysis file Editing, Coding, Scoring, Tabulating and Wilcoxon. Result of analysis using Wilcoxon test with ρ 0.05 shows that ρ = 0.000 <0.05, which means there Effect of counseling on high risk pregnancy to motivate pregnant women do antenatal care in Kembang Ringgit Pungging District of MojokertoThe results can be concluded research Capital has weak motivation in doing antenatal care prior to counseling, she has a strong motivation to perform anntenatal way after doing counseling and counseling on high risk pregnancy can increase the motivation of pregnant women in antenatal care doBased on the research results increase motivation antenatale maternal care during pregnancy determines the condition of the mother and fetus in the uterus so that complications during childbirth and pregnancy can be prevented.Keywords: Counseling, Pregnancy High Risk, Motivation, And Antenatale Care